Carboxylated-xyloglucan and peptide amphiphile co-assembly in wound healing. Issue 5 (11th August 2021) - Ajovalasit, Alessia; Redondo-Gómez, Carlos; Sabatino, Maria Antonietta; Okesola, Babatunde O; Braun, Kristin; Mata, Alvaro; Dispenza, Clelia
Abstract: Hydrogel wound dressings can play critical roles in wound healing protecting the wound from trauma or contamination and providing an ideal environment to support the growth of endogenous cells and promote wound closure. This work presents a self-assembling hydrogel dressing that can assist the wound repair process mimicking the hierarchical structure of skin extracellular matrix. To this aim, the co-assembly behaviour of a carboxylated variant of xyloglucan (CXG) with a peptide amphiphile (PA-H3) has been investigated to generate hierarchical constructs with tuneable molecular composition, structure, and properties. Transmission electron microscopy and circular dichroism at a low concentration shows that CXG and PA-H3 co-assemble into nanofibres by hydrophobic and electrostatic interactions and further aggregate into nanofibre bundles and networks. At a higher concentration, CXG and PA-H3 yield hydrogels that have been characterized for their morphology by scanning electron microscopy and for the mechanical properties by small-amplitude oscillatory shear rheological measurements and compression tests at different CXG/PA-H3 ratios. A preliminary biological evaluation has been carried out both in vitro with HaCat cells and in vivo in a mouse model.